(untitled) (Bangladesh Journal of Medical Science, 2024)
Aim The objective of this study is to examine collective foodborne illnesses (TIAC) reported in the province of Kenitra from 2019 to 2023, with the aim of determining the epidemiological profile and evaluating the effectiveness of the management measures implemented. On August 5, 2019, the survey therefore highlighted 9 cases (response rate of 75%), with an average age of 29 years and 75.5% women. Nausea, abdominal pain, diarrhea and vomiting were the main symptoms. The study revealed a significant correlation between the consumption of fish (75% attack rate), fries (90%) and soda (80%). Likewise, the study conducted on February 1, 2022 revealed a significant correlation between intoxication and consumption of soup (RR=1.4), chicken (RR=2.4), salad (RR= 1.62) and bread (RR=2.4). Rice presents a higher risk (RR=5.1, p=0.05). Levels of staphylococcus aureus were detected during microbiological analyses, exceeding acceptable thresholds. Faced with these findings, monitoring of food safety practices seems necessary. Preventing these outbreaks in the future would be most effective by improving food handling, storage and preparation methods. Bangladesh Journal of Medical Science Vol. 23 No. 04 October’24 Page : 1020-1029